Deep Learning and its Application for Healthcare Delivery in Low and Middle Income Countries - Williams, Douglas; Hornung, Heiko; Nadimpalli, Adi; Peery, Ashton (Frontiers in Artificial Intelligence, 2021)
As anyone who has witnessed first-hand knows, healthcare delivery in low resource settings is fundamentally different from more affluent settings. Artificial Intelligence, including Machine Learning and more specifically Deep Learning, has made amazing advances over the past decade. Significant resources are now dedicated to problems in the field of medicine, but with the potential to further the digital divide by neglecting underserved areas. In the general case, Deep Learning remains a complex technology requiring deep technical expertise. This paper explores advances within the more narrow field of deep learning image analysis that reduces barriers to adoption and allows individuals with less specialized software skills to effectively employ these techniques. This enables a next wave of innovation, driven largely by problem domain expertise and the creative application of this technology to unaddressed concerns in LMIC settings. The paper also explores the central role of NGOs in problem identification, data acquisition and curation, and integration of new technologies into healthcare systems.